Agronomic effect of soil tillage, no-tillage and crop rotation on yield of irrigated common bean - Silveira, Pedro Marques da; Silva, Osmira Fátima da; Stone, Luis Fernando; Silva, José Geraldo da (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this study was to evaluate the agronomic effect of soil tillage and crop rotation on grain yield of common bean (Phaseolus vulgaris L.) irrigated by central pivot. The study was conducted at the Embrapa-Centro Nacional de Pesquisa de Arroz e Feijão, in a Dark-Red Latosol with clay texture, during six consecutive years. Basic experiment was a 4 x 6 factorial, having a completely randomized block design with subdivided plots. Soil tillage systems were: P1 - moldboard plough (November-December), alternated with harrow disc (May-June); P2 - moldboard plough; P3 - harrow disc, and P4 - no-tillage. The crop rotations used were: R1 - rice-common bean; R2 - corn-common bean; R3 - soybean-wheat; R4 - soybean-wheat-soybean-common bean-rice-common bean; R5 - rice associated with Calopogonium mucunoides-common bean; and R6 - corn-common bean-corn-common bean-rice-common bean. The crop rotations R1, R2, R3, and R5 were annual and R4 and R6 were triennial; in this study, only rotations with common bean were evaluated. Rice, corn and soybean were sown in November/December (summer) and common bean and wheat in May/June (winter). Grain yield of common bean was influenced by soil tillage and crop rotation. Yield was higher under soil prepared with moldboard plough in combination with summer sowing and prepared with harrow disc in winter sowing. Common bean grain yield was higher when biannual sowing was done in the same area in rotation with rice/C. mucunoides and rice, and lower in rotation with corn. Irrigated common bean crop was economically viable as a function of soil tillage and crop rotation and economic return varied from 67% to 97%.